A metodologia ativa da aprendizagem baseada em problemas éticos no ensino jurídico - ALVES, Luis Henrique Ramos (2023)
The present dissertation, inserted in the Graduate Program in Education of the Universidade do Oeste Paulista (UNOESTE), in the research line Training and Pedagogical Practice of the Teaching Professional, aimed to analyze the strategy of the active methodology of problem-based learning for the understanding of ethical curricular content in legal education. This objective was born from the hypothesis that traditional and expository legal ethical teaching does not meet the training requirements of the Law professional. The approach used for this research was the qualitative intervention type. Eighteen students from the discipline General and Professional Ethics of the Law course enrolled in the 10th morning term and their respective teacher participated. Data collection and the context of the research took place at a private university in the State of São Paulo. In order to carry out the ProblemBased Learning methodology, two problems involving the legal ethics discipline were elaborated: the first problem deals with the discussion about ethical infractions and disciplinary sanctions and the second problem dealt with respect for the rights of lawyers from an ethical point of view. For data collection, we used the observation of the PBL process, in addition to the documentary analysis of the records made in BeActive, as well as a focus group in which the research participants reflected on the process experienced, and an interview with the discipline professor. Through analysis with data triangulation in the light of the theoretical framework, four thematic axes were created: 1. Development of students' competence and the construction of group work in the discipline; 2. Problem solving ability; 3. Validation of the PBL by the students through the Focus Group; 4. Validation of the PBL by the teacher. The data analysis showed, in relation to the first thematic axis, that the use of the active methodology of learning based on ethical problems in legal education provided the construction of knowledge about the contents worked by the students, as well as helped in the development of a collaborative teaching among students in teamwork, thus generating a democracy within the application, so that students had the opportunity to also learn to listen, speak and position themselves in face of problem situations. Regarding the second axis, it was possible to conclude that the students evolved in their procedural skills and started to have an active posture in face of the problems presented, being extremely important for the development of the evolution of thought, in the creation procedure and in the activity to seek the necessary ideas. Regarding the third thematic axis, it was possible to conclude, through the perceptions expressed by the students during the focus group, that the active methodology of problembased learning can significantly contribute to the construction of knowledge, given that the results were achieved, and it was evident that students have the ability to be protagonists in the construction of their knowledge autonomously. In the last axis, through the perceptions shared by the professor responsible for the discipline, we concluded that the application of the methodology went beyond what was expected, and the possibility of its application was validated.